ANALISA ZAT PEWARNA RODHAMIN B PADA KERUPUK KENTANG DIJUAL DI KENJERAN - Hayati, Mala (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
ANALISA ZAT PEWARNA RODHAMIN B PADA KERUPUK KENTANG DIJUAL DI KENJERAN Mala Hayati, S.TP., M.Kes.Prodi D3 Analis Kesehatan UM SurabayaÂ AbstractDyes are dyes food that can improve or members of colors in food. With the addition of color to the food, the food is not going to be colored to look more attractive and striking colored. There are two types of food coloring are allowed and which are not permitted, especially that are not allowed are dye rodhamin B. Rodhamin B is colored crystal powder greenish, purplish red. In many areas the selling crackers Kenjeran bright red potatoes. Therefore, this study was conducted with the aim to know the content of dyes Rodhamin B on potato chips sold in Kenjeran. This research is descriptive, ie to obtain a description of the content Rodhamin B were analyzed from sample examination bright red. Samples were potato chips sold in Kenjeran Surabaya. Total sample of 30 potato chips. Based on the results of prenatal Rodhamin B on potato chips sold dikenjeran Surabaya. Of the 30 samples obtained potato chips containing Rodhamin B 33%, while that does not contain Rodhamin B 67%, the percentage of the results obtained more crackers that do not use Rodhamin B, but still there are 33% who use Rodhamin B should not be allowed because of the dye Rodhamin B dyes are prohibited and may cause health problems of our bodies. Keyword: Rodhamin B, Crackers potatoes